Antibiotic adverse effects in pediatric acute rhinosinusitis: Systematic review and meta-analysis. (May 2022) - Axiotakis, Lucas G.; Szeto, Betsy; Gonzalez, Joseph N.; Caruana, Francesco F.; Gudis, David A.; Overdevest, Jonathan B.
Abstract: Background: Pediatric acute bacterial rhinosinusitis (ABRS) is often treated with oral antibiotics, with limited insight into adverse effects (AEs) across drug classes. In this systematic review and meta-analysis, we characterize AE incidence associated with oral antibiotics in these patients. Methodology/Principal: We searched PubMed and Embase for English-language articles published from 1985 to September 2020 reporting AEs of oral antibiotic therapy for ABRS patients aged 0–18 years. Six-hundred and sixty-six articles underwent title and abstract screening, identifying 154 articles for full-length review. Results: Eleven articles were included, most of which reported individual and aggregate AE incidences. Amoxicillin/clavulanate, amoxicillin, cephalosporin/carbacephem, and placebo groups were identified. Random-effects meta-analysis of prospective groups identified appreciable incidences of diarrhea and abdominal pain, and low incidence of rash, for amoxicillin-clavulanate and amoxicillin. All antibiotics as well as placebo were associated with non-zero overall AE incidence. Children receiving antibiotics were about twice as likely to incur any AE during treatment in placebo-controlled studies, though this association was not significant. High heterogeneity limited most point estimates, with risk of bias, typically in outcomes measurement, detected in most studies. Conclusions: Reporting of AEs associated with oral antibiotic use in pediatric ABRS is limited in current literature. Adverse effects are non-negligible, but may not significantly exceed placebo. Highlights: Adverse events with oral antibiotic use in pediatric acute bacterial rhinosinusitis are low. Diarrhea and abdominal pain are the most common adverse events; rash is relatively uncommon. Adverse event rates for placebo and antibiotic groups are comparable, suggesting that some adverse events may be sequelae of ARBS infection. Standardization of AE measurement and reporting methods would facilitate tracking of true adverse event incidence for common antibiotics.